Low-Cost, Scalable Simulations in Obstetric Trauma and Resuscitative Hysterotomy for Emergency Medicine Residents - Hao Ren Chin; Wei Xiang Ng (Association of American Medical Colleges, 2024)
Introduction Simulation-based learning is essential for health care providers to prepare for rare obstetric emergencies, such as severe trauma and maternal cardiac arrest. These situations demand rapid and prompt actions, often testing the skill of emergency physicians. Resuscitative hysterotomy (RH), a critical procedure in maternal cardiac arrest, requires technical expertise, coordination, and anatomical knowledge. The high cost of commercial trainers and complex existing models restricts accessibility. This resource introduces a low-cost anatomically accurate RH task trainer and assesses its effectiveness in improving skills and confidence among trainee emergency physicians. Methods A 20-minute-long case scenario depicted the resuscitation of a pregnant trauma patient with tension pneumothorax and uterine rupture, culminating in maternal cardiac arrest necessitating RH. Residents performed RH on the task trainer under faculty guidance. Feedback followed the Pendleton model, and an online questionnaire gauged the residents' experiences. Results Thirty emergency medicine residents participated in the simulation. The questionnaire revealed positive responses, confirming the session's relevance and enhancement of clinical skills and confidence. Discussion Our results underscore the RH task trainer's critical role in improving residents' skills and confidence during obstetric trauma simulations. Its realism and effectiveness were notably well received. Future refinements aim to augment fidelity while preserving affordability and integrating regular reinforcement sessions. This innovative educational approach equips health care professionals to respond adeptly to rare and challenging obstetric emergencies, ultimately elevating outcomes for mothers and infants during critical situations.